Extracting the cation distributions in NiFe2−xAlxO4 solid solutions using magnetic Compton scattering. (16th October 2015) - Kamali, S; Shih, K; Barbiellini, B; Wang, Y J; Kaprzyk, S; Itou, M; Bansil, A; Sakurai, Y
Abstract: We discuss the ground state electronic structure and magnetization properties of a series of NiFe2− x Al x O4 solid solutions ( x   =  0.0, 0.4, 0.8, 1.2, 1.6, and 2.0) using magnetic Compton scattering measurements, together with parallel first-principles computations. In this way, we systematically extract the complicated cation distributions in this ferrite system as a function of x . The relationship between the electronic ground state, magnetism, and cation distributions is explained in terms of a model, validated by our first-principles computations, wherein the magnetic properties of the three cation distributions are assumed to be different. A good accord is found between the computed and measured magnetic Compton profiles.